Outside the Bible, 3-volume set : Ancient Jewish Writings Related to Scripture (Book collections on Project MUSE., 2013)
"An anthology of key texts of ancient Jewish literature from the Second Temple period, including commentary that links to the development of both Rabbinic Judaism and Early Christianity"--